The benefits of physical activity and exercise on physical, cognitive and daily life activities in aging adults - Zerbo, Dorjana (Annales Kinesiologiae, 2019)
Due to increased longevity, degenerative diseases and disabilities have become one of the largest health-care problems. The state of well-being with a low risk of premature health problems is important for successful aging. Even if the impact of physical activity and exercise on performance of daily life activities is still poorly understood, it seems that regular training has important benefits on physical and cognitive functioning in healthy elderly population. Combined training, including strength, balance, flexibility exercises and activities that improve cardiorespiratory fitness, are important to ensure the independency of elderly people.